Project Management Methodologies: Selecting, Implementing, and Supporting Methodologies and Processes for Projects - Charvat, Jason (John Wiley & Sons, 2011)
Presents a comprehensive survey of the tools, tips, techniques, and tactics that are available to guide project managers to the successful completion of their projects.